Effects of low birth weight on lung function in children and adolescents: A review - Neto, Pedro Martins Lima; Andrade Paes, Antônio Marcus de; Propp Lima, Raina Jansen Cutrim; Lucena Batista, Rosângela Fernandes; Santos, Alcione Miranda dos; Simões, Vanda Maria Ferreira (International Journal of Advanced Engineering Research and Science, 2022)
In this study, we aimed to carry out an integrative review of studies that assessed the effects of low birth weight on pulmonary function in children and adolescents. A total of 18 out of 64 retrieved articles were included in this review. The sample size totaled 3,409 children and adolescents distributed into case and control groups. Spirometric assessment was held at ages ranging from 5 to 18 years. In three studies, assessments were performed more than once at different ages. Most studies were carried out in Europe. In all studies, at least one of the spirometric measurements was reduced, with end-expiratory volume in one second being the most frequent. Low birth weight appears to negatively influence lung function in children and adolescents, and the effects of this impairment may be long-lasting and persist through other stages of life.